miR-150-5p and XIST interaction controls monocyte adherence: Implications for osteoarthritis therapy - Wang, Yu-Han; Tsai, Chun-Hao; Liu, Shan-Chi; Chen, Hsien-Te; Chang, Jun-Way; Ko, Chih-Yuan; Hsu, Chin-Jung; Chang, Ting-Kuo; Tang, Chih-Hsin (Frontiers in Immunology, 2022)
Recent literature points out the importance of microRNAs (miRNAs) functioning as diagnostic biomarkers and therapeutic agents in osteoarthritis (OA) and regulating gene expression. In OA pathogenesis, cell adhesion molecules (CAMs), especially vascular cell adhesion protein 1 (VCAM-1), recruit monocyte infiltration to inflamed synovial tissues and thus accelerate OA progression. Up to now, little is known about the regulatory mechanisms between miRNAs as well as long non-coding RNAs (lncRNAs) and VCAM-1 during OA progression. This article emphasizes the functional feature of miR-150-5p that interact with the lncRNA X-inactive specific transcript (XIST) to control VCAM-1-dependent monocyte adherence in OA synovial fibroblasts (OASFs). Synovial tissue samples and OASFs showed high expression of VCAM-1, CD11b (a monocyte marker) and XIST, and lower levels of miR-150-5p in synovial tissue from OA patients compared with non-OA individuals. XIST enhanced VCAM-1 dependent monocyte adherence to OASFs. Upregulation of miR-150-5p inhibited the XIST-derived effect on monocyte adherence. Furthermore, we found that administration of miR-150-5p effectively ameliorated OA severity in the anterior cruciate ligament transection (ACLT) model. The interaction of miR-150-5p and XIST regulated VCAM-1-dependent monocyte adherence and attenuated OA progression. Our finding provides a promising molecule therapeutic strategy for OA.